Primary Care Practitioners’ Views on Incorporating Long-term Prognosis in the Care of Older Adults - Schoenborn, Nancy L. (JAMA Intern Med, 2016)
IMPORTANCE: Clinical practice recommendations increasingly advocate that older patients’ life expectancy be considered to inform a number of clinical decisions. It is not clear how primary care practitioners approach these recommendations in their clinical practice. OBJECTIVE: To explore the range of perspectives from primary care practitioners on long-term prognosis, defined as prognosis regarding life expectancy in the range of years, in their care of older adults. DESIGN, SETTING, AND PARTICIPANTS: A qualitative, semistructured interview study was conducted in a large group practice with multiple sites in rural, urban, and suburban settings. Twenty-eight primary care practitioners were interviewed; 20 of these participants (71%) reported that at least 25% of their patient panel was older adults. The audiorecorded discussions were transcribed and analyzed, using qualitative content analysis to identify major themes and subthemes. The study was conducted between January 30 and May 13, 2015. Data analysis was performed between June 10 and September 1, 2015. MAIN OUTCOMES AND MEASURES: The constant comparative approach was used to qualitatively analyze the content of the transcripts. RESULTS: Of the 28 participants, 16 were women and 21 were white; the mean (SD) age was 46.2 (10.3) years. Twenty-six were physicians and 2 were nurse practitioners. Their time since completing clinical training was 16.0 (11.4) years. These primary care practitioners reported considering life expectancy, often in the range of 5 to 10 years, in several clinical scenarios in the care of older adults, but balanced the prognosis consideration against various other factors in decision making. In particular, patient age was found to modulate how prognosis affects the primary care practitioners’ decision making, with significant reluctance among them to cease preventive care that has a long lag time to achieve benefit in younger patients despite limited life expectancy. The participants assessed life expectancy based on clinical experience rather than using validated tools and varied widely in their prognostication time frame, from 2 years to 30 years. Participants often considered prognosis without explicitly discussing it with patients and disagreed on whether and when long-term prognosis needs to be specifically discussed. The participants identified numerous barriers to incorporating prognosis in the care of older adults including uncertainty in predicting prognosis, difficulty in discussing prognosis, and concern about patient reactions. CONCLUSIONS AND RELEVANCE: Despite clinical recommendations to increasingly incorporate patients’ long-term prognosis in clinical decisions, primary care practitioners encounter several barriers and ambiguities in the implementation of these recommendations.